Eco-art sculpture for primary school children: artistic approaches in integrating art education with environmental awareness / Fadzlina Mohd. Akhir - Mohd. Akhir, Fadzlina (2013)
Eco-art as for children was an activity in which children negotiated between the environmental awareness and adult art world. In the developed process, they transformed the art making practices into activities that was meaningful and fun. This Case Study focuses on the making of an eco-art sculpture as a means for students to understand the environmental awareness. The purpose of this study is to examine the artistic approaches in integrating Art Education with environmental awareness through the making of an eco-art sculpture. Each student will be producing a sculpture that emphasizes on the use of discard materials as their main media. Sculpture produced will be an expression of students on the environmental problem which deemed as a major social issue. Art Education emerged as a way of learning of how to value the authentic beauty of environment. Through the process of art making, children can portray their understanding and awareness of the environmental issue in the artistic and varied ways. The children's understanding of environmental awareness will be concluded not only through their work of art, but also their ability to criticize the work. Series of observation and interviews were conducted on six volunteered students from various backgrounds, learning behaviour and perspectives towards environmental concerns. This study contributes to the development of the education model that takes into consideration the environmental, aesthetic and comprehensive approach to life.